Pemanfaatan Limbah Sabut Kelapa Menjadi Komoditas Kerajinan Bagi Masyarakat dan UMKM di Kecamatan Gaung Anak Serka Kabupaten Indragiri Hilir - Hermita, Neni; Ernidawati, Ernidawati; Hasanuddin, Hasanuddin; Zulkarnain, Zulkarnain; Fakhruddin, Fakhruddin; Idris, Idris; Dhuha, Nur Adh; Satria, Defni; Inayah, Nisywatul; Adha, M. Radiva; Wiguna, M. Alfatah Putra; Yustika, Ira; Mawaddah, Ira; Malayani, Bela; Siregar, Sari Wahyuni; Zelita, Nuri; Hanifa, Nurul; Yunita, Milla; Sihombing, Yogi Hasan; Gussaf, Saskia Amanda; Pratama, Thomas Kurnia; Ningsih, Winda Prasetia; iman, Khairul; Ardiyansah, Ari; Wati, Almustika; Febriani, Egia; Alataf, Azahrah Aprila (Unri Conference Series: Community Engagement, 2024)
Utilization of coconut fiber waste into craft commodities for UMKM in Gaung Anak Serka District, Indragiri Hilir Regency, aims to improve community skills, create economic opportunities, and reduce coconut fiber waste. This activity involves training on processing techniques, making flower pots, and effective marketing strategies. This Community Service Activity uses the Service Learning (SL) approach, which consists of several stages, namely identification of community problems or needs, integration of academic learning, community service, collaboration with community partners, reflection and evaluation, and continuous learning. Overall, the response from participants was very good, namely 86.50%. This shows an increase in participant knowledge and skills, which contributes to increased income through marketed flower pots. In addition, this program encourages continuous learning and collaboration between the community, UMKM actors and universities to support innovation. Thus, the utilization of coconut fiber waste not only provides economic benefits but also contributes to environmental sustainability and community and UMKM development.